2020
DOI: 10.21511/ppm.18(2).2020.16
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting accrual accounting reform and transparency of performance in the public sector in Vietnam

Abstract: This study was conducted to determine the factors and their influence on accrual accounting reform in the public sector in Vietnam. Combining qualitative and quantitative research methods based on empirical surveys of 268 accountants, controllers, and auditors working in state agencies such as the Department of Finance, state treasuries and agencies receiving revenues from the state budget in 2019. This study shows that six factors influence the reform of the accounting system in the public sector in Vietnam t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In developing countries, authorities and regulators show resistance to adopting change, as the majority of public sector accountants are not trained and qualified for the implementation of the accrual-based IPSAS. Previous studies demonstrated that neither workers nor management have adequate financial and human resources for the implementation of the accrual-based IPSAS, which leads to the top management withholding commitment to the implementation of the accrual-based IPSAS (Ahmad and Nasseredine, 2019; Azevedo et al , 2020a, 2020b; Harun, 2007; Ismaili and Ismajli, 2020; Tetteh et al , 2021; Thanh et al , 2020; Yuliati et al , 2019). The resistance to change is one of the barriers (Al-otoom and Alrabba, 2022; Brito and Jorge, 2021; Tetteh et al , 2021) because the age of senior managers has a negative impact on accounting implementation (Neves and Gómez-Villegas, 2020) for fear of losing control over the budget authority (Adhikari et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In developing countries, authorities and regulators show resistance to adopting change, as the majority of public sector accountants are not trained and qualified for the implementation of the accrual-based IPSAS. Previous studies demonstrated that neither workers nor management have adequate financial and human resources for the implementation of the accrual-based IPSAS, which leads to the top management withholding commitment to the implementation of the accrual-based IPSAS (Ahmad and Nasseredine, 2019; Azevedo et al , 2020a, 2020b; Harun, 2007; Ismaili and Ismajli, 2020; Tetteh et al , 2021; Thanh et al , 2020; Yuliati et al , 2019). The resistance to change is one of the barriers (Al-otoom and Alrabba, 2022; Brito and Jorge, 2021; Tetteh et al , 2021) because the age of senior managers has a negative impact on accounting implementation (Neves and Gómez-Villegas, 2020) for fear of losing control over the budget authority (Adhikari et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…However, the limited financial resource constraint is mentioned much more in studies conducted in developing countries (Ademola et al , 2020; Ahmad and Nasseredine, 2019; Azevedo et al , 2020a, 2020b). In other words, developing countries have major difficulties in getting adequate infrastructure and the human and financial resources to apply the standards (Brusca et al , 2016; Harun et al , 2021; Shehadeh, 2022; Thanh et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation